2012
DOI: 10.22179/revmacn.14.206
|View full text |Cite
|
Sign up to set email alerts
|

Diet and ecomorphology of the ichthyofauna of Manantiales stream, Buenos Aires province, Argentina

Abstract: Diet and ecomorphology of the ichthyofauna of Manantiales stream, Buenos Aires province, Argentina. the present study addresses the correlation between diet and morphology of 19 fish species that inhabit the Manantiales stream at the headwaters of the samborombón river, Buenos Aires province, Argentina. the species were classified into four trophic groups: carnivores, omnivores, insectivores and detritivores-alguivores. twelve ecomorfologic attributes related to habitat use and feeding patterns were analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 37 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…However, in our study, no significant differences were observed in size between males and females. This observation could potentially be attributed to the differences between studies conducted in a natural environment, [39][40][41] in contrast to controlled environmental conditions under which the fish were reared.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, no significant differences were observed in size between males and females. This observation could potentially be attributed to the differences between studies conducted in a natural environment, [39][40][41] in contrast to controlled environmental conditions under which the fish were reared.…”
Section: Discussionmentioning
confidence: 99%